Infiltration capacity based on soil geophysical constants using artificial infiltration in residential land - Andayono, Totoh; Mera, Mas; Junaidi, Junaidi; Dalrino, Dalrino (Teknomekanik, 2024)
Conversion of catch-land into residential land in urban areas reduces infiltration, and increases surface flow and flood risk. Artificial infiltration is a potential solution to increase infiltration capacity, but its effectiveness is highly dependent on the physical characteristics of the soil, including geophysical constants. This study aims to determine the level of infiltration capacity based on the value of soil geophysical constants using artificial infiltration in residential land in Padang. Measurements were carried out using the Horton method and double-ring infiltrometer in several residential locations. The study results show that the soil characteristics of residential land in Padang consist of the soil texture of sand, loamy sand, and sandy loam, which have high moisture content, large fill weight, and low porosity, causing low infiltration rate and high surface flow. Artificial infiltration can significantly increase the infiltration capacity, especially on sandy soils with high hydraulic conductivity. The soil geophysical constant, k, is classified according to field measurement results. In the lower range of 1.2 < k ≤ 1.9, the average infiltration capacity was found at 625.1 mm/hour. Within the interval of 1.9 < k ≤ 2.6, the mean capacity decreased to 587.7 mm/hour, but in the upper interval of 2.6 < k ≤ 3.3, the average infiltration capacity was 499 mm/hour. Large soil geophysical constants reveal higher infiltration capacity, while small geophysical constants indicate low infiltration capacity.